Copper-catalyzed ortho-halogenation of arenes and heteroarenes directed by a removable auxiliary1. Issue 24 (25th March 2015) - Li, Bo; Liu, Bin; Shi, Bing-Feng
<x xml:space="preserve">Abstract</x> Copper-catalyzed ortho-halogenation of C(sp2)–H bonds directed by a PIP directing group with NXS (X = Cl, Br, I) has been developed. The reaction is scalable and tolerates a broad range of functional groups and heteroarenes, providing an efficient access to halogenated arenes and heteroarenes.